Cardioprotective Therapy in the Practice of an Anaesthesiologist - Balan A. V. (Interactive science, 2020)
all components of anaesthesia have a direct or indirect depressing effect on the myocardium and functional activity of the brain. Given the initial failure of the coronary blood flow, life-threatening disorders of the heart are possible. The higher the severity of the underlying disease, the greater the risk of transient neurological deficit, stroke. Extended continuous monitoring of vital functions, careful assessment of the neurological status of the patient with special attention to the level of consciousness, the presence or absence of symptoms of increased ICP is necessary. The purpose of this study is to evaluate the beneficial effect of cardioprotectors Mexicor, Meldonium in the fight against ischemia in patients with CHD, GB in the department of surgical profile. The following methods have been used: review of literature, previously published research papers. Results: this article discusses the main drugs with cardioprotective properties, describes the positive experience of using them by specialists, and proves the effectiveness of using drugs in the long term.
Keywords: антиоксиданты; мельдоний; Meldonium; ишемия; ischemia; нарушения ритма; милдронат; нарушения метаболизма; антигипоксанты; метаболическое средство; Mildronate; rhythm disorders; metabolic disorders; antioxidants; antihypoxants; metabolic agent